2006
DOI: 10.1016/j.jhevol.2005.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Limb bone bilateral asymmetry: variability and commonality among modern humans

Abstract: Humans demonstrate species-wide bilateral asymmetry in long bone dimensions. Previous studies have documented greater right-biases in upper limb bone dimensionsdespecially in length and diaphyseal breadthdas well as more asymmetry in the upper limb when compared with the lower limb. Some studies have reported left-bias in lower limb bone dimensions, which, combined with the contralateral asymmetry in upper limbs, has been termed ''crossed symmetry.'' The examination of sexual dimorphism and population variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
441
8
20

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 408 publications
(522 citation statements)
references
References 78 publications
(82 reference statements)
53
441
8
20
Order By: Relevance
“…This limitation was mitigated by using a systematic method and high-resolution pictures (degree of error \ 1 mm), and by using a projection that is used clinically (AP). Additionally, the measured asymmetry of the femoral head in this study falls within that reported in the literature (Table 8) [3,21,28,45].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This limitation was mitigated by using a systematic method and high-resolution pictures (degree of error \ 1 mm), and by using a projection that is used clinically (AP). Additionally, the measured asymmetry of the femoral head in this study falls within that reported in the literature (Table 8) [3,21,28,45].…”
Section: Discussionsupporting
confidence: 87%
“…The investigators who have examined symmetry have studied bone properties and cortex thickness [28,32,36,40], with few studying dimensions [3,28]. The clinical impact of asymmetry is subtle, as the assumption of symmetry is pervasive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We report normal bone morphology in the mosaic father, evaluated by DXA scan and HR‐pQCT. The asymmetry in body composition with slightly reduced size of left‐sided extremities in the father is unlikely to result from the OI mosaicism as this phenomenon may be due to a number of factors 19 and is not a distinctive feature of OI.…”
Section: Discussionmentioning
confidence: 99%